Human Capital Quality and Marketing Performance: A Strategic Management Perspective - Aswin, Ullya Rahmi; Sari, Fitrah; Gustina, Leni (SAFE-Network, 2026)
This study examines the influence of human capital quality on marketing performance from a strategic management perspective. In an increasingly competitive business environment, organizations are required to leverage internal strategic resources to achieve superior marketing outcomes. Human capital quality, reflected in employees’ knowledge, skills, experience, and capabilities, is considered a critical intangible asset that supports effective marketing strategy implementation. This research employs a quantitative explanatory approach using a survey method. Data were collected through structured questionnaires distributed to employees and managers involved in marketing and strategic functions within business organizations. The data were analyzed using descriptive statistics and regression analysis to test the proposed relationship between human capital quality and marketing performance. The results indicate that human capital quality has a positive and statistically significant effect on marketing performance, demonstrating that organizations with higher-quality human resources tend to achieve better marketing outcomes, including sales growth, customer acquisition, and market competitiveness. These findings confirm that marketing performance is not only shaped by external market conditions but is also strongly influenced by internal strategic resources. The study concludes that human capital quality plays a crucial role in enhancing marketing performance and should be integrated into organizational strategic and marketing planning. The results provide valuable insights for managers in aligning human resource development with marketing objectives to achieve sustainable competitive advantage.